Tribological Aspects of Graphene and Its Derivatives - Çağla Gizem Acar; Audrius Žunda (Lubricants, 2025)
Tribology is the branch of science and engineering that focuses on understanding friction, wear, and lubrication, which is essential for saving energy, improving performance, reducing vibration, and creating eco-friendly lubricants and wear resistance. Over the past decade, nanomaterials have captured the immense interest of tribology science. This review aimed to analyze how graphene and its derivatives can be incorporated into lubricants to enhance their properties, particularly in mitigating friction and wear. This is due to graphene’s excellent specific properties, such as a low friction coefficient, mechanical strength, high thermal and electrical conductivity, biocompatibility, high load-carrying capacity, wear resistance, and chemical stability. This study briefly introduces graphite, graphene, and graphene oxide, as well as presents graphene as a material for tribological applications. Among other things, the environmentally friendly possibilities of chemical reduction of reduced graphene oxide are analyzed here, as well as the macro-, micro-, and nano-tribological examination of graphene and its derivatives. Despite what is already known about graphene in tribology, further research is needed to gain a deeper understanding of development regarding integration with different materials, long-term performance, eco-friendly synthesis using green reducing agents, and comprehending how these approaches may affect systems at various scales.